ACCELERATING DIGITAL TRANSFORMATION THROUGH SERVERLESS ARCHITECTURE - Venkata Raghavendra Vutti, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The rise of serverless technologies is fundamentally changing modern application development and how companies create, implement, and scale their apps. Examining both theoretical underpinnings and actual implementations, this thorough technical article investigates the transforming effect of serverless architectures on application development. It examines the technical components, design patterns, and operational concerns guiding successful implementations from conventional monolithic structures to serverless architectures. This article addresses the difficulties companies experience during migration as well as important elements such as event-driven architecture, state management tactics, security consequences, and cost optimization techniques. Through analysis of actual case studies and new trends, this article offers technical leaders and developers with practical insights for using serverless technologies to attain enhanced development efficiency, lowered operational complexity, and improved scalability. The article gives readers a complete plan for evaluating and using serverless technologies in their transformation projects. It does this by focusing on practical implementation strategies, monitoring solutions, and how to connect serverless architectures to existing systems.